2001
DOI: 10.1111/j.1349-7006.2001.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Differentially Expressed Genes in 5‐Fluorouracil‐resistant Human Gastrointestinal Tumor Cells

Abstract: To identify genes differentially expressed in association with resistance to 5-fluorouracil (5FU), an mRNA differential display (DD) analysis was used to compare transcripts from the NUGC-3 human gastric tumor cell line and the NUGC-3/5FU/L line, which had acquired 208-fold resistance as a consequence of repeated exposure to escalating concentrations of 5FU. The 110 cDNA fragments differentially expressed in the DD analysis of either the NUGC-3 or NUGC-3/5FU/L cells were sequenced and subjected to a homology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…16 Therefore, a certain degree of crossover between acquired resistance and inherent resistance to 5-FU may exist. In addition, the pharmacogenetic variability of 5-FU-related enzymes, such as TS, DPD and OPRT (the expressions of which varied little in our cell lines 17 ), might be a major determinant of variations in the outcome of colorectal cancer patients treated with 5-FU; thus, these genes were added to our candidate genes, which were then validated using RT-PCR in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…16 Therefore, a certain degree of crossover between acquired resistance and inherent resistance to 5-FU may exist. In addition, the pharmacogenetic variability of 5-FU-related enzymes, such as TS, DPD and OPRT (the expressions of which varied little in our cell lines 17 ), might be a major determinant of variations in the outcome of colorectal cancer patients treated with 5-FU; thus, these genes were added to our candidate genes, which were then validated using RT-PCR in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is not immediately obvious why this variant would be associated with CpG island methylation frequency, other than through a possible link with the concentration of intracellular folate intermediates. In support of this, in vitro studies in colorectal and gastric cell lines have shown a link between MTHFD1 expression and sensitivity to 5-fluorouracil (19,20). Further research is required, however, to evaluate DNA methylation and intracellular folate levels in relation to the MTHFD1 G1958A polymorphism in normal and tumour tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the increased expression of thymidine kinase, equilibrative nucleoside transporter 1, and methylenetetrahydrofolate dehydrogenase, as well as the decreased expression of orotate phosphoribosyltransferase, thymidine phosphorylase, uridine phosphorylase, cytidine deaminase, and integrin alpha 3 were correlated with a 5-fluorouracil-resistant phenotype of gastric cancer cells [20,21]. In another report, overexpression of annexin I and thioredoxin was found to be associated with daunorubicin-resistance, and overexpression of thioredoxin was found to be associated with mitoxantrone-resistant phenotypes of gastric cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%